La danse : comment on dansait, comment on danse - Charbonnel, Raoul, 1872-1946; Bernay, Berthe, 1856-; Casadesus, Francis, 1870-1954; Maugué, Jules, 1869-1953 (Paris : Garnier frères, 1899)
This manual is an extensive history of dance that incorporates many countries, cultures, and periods including Chinese, Hindu, Egyptian, Greek, ancient Gaul, European Renaissance, and Baroque. The manual also covers popular culture, peasant dance, and "foreign dance." The perspective of this manual is clearly nineteenth century, with little emphasis on historical fact. The point of view is clearly western, and this is evident in the music examples that accompany almost every country or culture's entry--all have been subjected to western notation and are arranged in late nineteenth-century grand musical style. Additionally, the text includes numerous illustrations and, no matter the country or culture, the figures are physically shaped to look like late nineteenth-century western ladies and gentlemen.
Available also through the Library of Congress Web site as facsimile page images and full text.
Keywords: Dance History and Theory; Dance -- History; Music for Dance; Theatrical Dance